A proposed model for achieving quality in information systems projects - Hani Abdulrahim Ali Alshinawi (International Journal of Computers and Informatics, 2024)
This research is concerned with how to achieve quality in information systems projects, so it focuses on proposing a model for ensuring quality for managing information systems projects. This paper presents some important concepts related to this field. It also presents the stages and activities of managing information systems projects. This paper presents a set of proposed steps to achieve each activity of planning information systems projects. Based on the proposed steps and a set of statistical techniques, this paper presents a proposed model for ensuring quality for information systems project management activities. This proposed model can be used to build an integrated guide to achieve higher levels of excellence in performance for information systems project managers. This guide can be applied to projects of all sizes, whether small, medium or large.